Dietary Antioxidant Indices in Relation to All-Cause and Cause-Specific Mortality Among Adults With Diabetes: A Prospective Cohort Study - Wang, Wenjie; Wang, Xiaoyan; Cao, Shiling; Duan, Yiting; Xu, Chengquan; Gan, Da; He, Wei (Frontiers in Nutrition, 2022)
Background: The potential beneficial effect of individual antioxidants on mortality have been reported. However, the association of overall intakes of dietary antioxidants with all-cause and cause-specific mortality among adults with diabetes remained unclear. Methods: A total of 4,699 US adults with diabetes were enrolled in 2003-2014 in the National Health and Nutrition Examination Survey (NHANES), and followed for mortality until 31st December 2015. Dietary Antioxidant Quality score (DAQs) and Dietary Antioxidant Index (DAI), which indicate the total antioxidant properties, were calculated based on the intakes of vitamin A, C, E, zinc, selenium and magnesium. Cox proportional hazard models was used to investigate the associations of DAQs or DAI with all-cause and cause-specific mortality. Results: A total of 913 deaths occurred during 27,735 person years of follow-up, including 215 deaths due to CVD and 173 deaths due to cancer. The higher intakes of antioxidant vitamin A, E, magnesium and selenium were associated with lower all-cause mortality. The adjusted HRs (95% CIs) comparing the highest DAQs (5-6) to the lowest DAQs (0-2) were 0.70 (0.53-0.92) for all-cause mortality, 0.56 (0.35-0.90) for CVD mortality, and 0.59 (0.33-1.04) for cancer mortality. Consistent inverse associated were found between DAI and mortality. Conclusion: Higher intake of overall dietary antioxidants was associated with lower all-cause and CVD mortality in adults with diabetes. Future dietary intervention studies are needed to determine whether increasing antioxidant overall micronutrients intake could prevent premature death among adults with diabetes.